Mirror therapy in children with hemiparesis: a randomized observer‐blinded trial. (5th April 2016) - Bruchez, Roselyn; Jequier Gygax, Marine; Roches, Sylvie; Fluss, Joel; Jacquier, David; Ballabeni, Pierluigi; Grunt, Sebastian; Newman, Christopher J
Abstract : Aim: To determine the efficacy of mirror therapy in children with hemiparesis. Method: The design was an observer‐blinded parallel‐group randomized controlled trial (International Standard Randomised Controlled Trial Number 48748291). Randomization was computer‐generated, 1:1 allocation to mirror therapy or comparison groups. The settings were home‐based intervention and tertiary centre assessments. Participants were 90 children with hemiparesis aged 7 to 17 years. Intervention was 15 minutes per day of simultaneous arm training, 5 days a week, for 5 weeks. The mirror therapy group used a mirror; those in the comparison group looked at their paretic limb. Assessments comprised measures of upper limb strength, function (Melbourne Assessment 2), daily performance (ABILHAND‐Kids), and sensory function at weeks 0 ( T 0 ), 5 ( T 1 ), and 10 ( T 2 ). Results: There were no significant differences in outcomes and their progression over time between the mirror therapy and comparison groups. Post‐hoc intention‐to‐treat analyses showed significant improvements in both groups for grasp strength ( T 0 − T 1 +12.6%), pinch strength ( T 0 − T 2 +9.1%), upper limb function in terms of accuracy ( T 0 − T 2 +2.7%) and fluency ( T 0 − T 2 +5.0%), as well as daily performance ( T 0 − T 2 +16.6%). Per protocol analyses showed additional improvements in dexterity ( T 0 − T 2 +4.0%). Interpretation: The use of the mirror illusion during therapy had no significant effect on treatment outcomes. However, 5 weeks of daily simultaneous arm training significantly improved paretic upper limb strength, function, and daily use. What this paper adds: The mirror illusion has no therapeutic effect in children with hemiparesis. Simultaneous arm training improves strength, function, and daily use. Video Podcast:https://youtu.be/5PdCjZlCy6c